Asymptotic optimality of sequential designs for estimation. (1995) - Rekab, Kamel
Abstract : This paper is concerned with the problem of allocating a fixed number of trials betweenK independent populations from the exponential family, in order to estimate a linear combination of the means with squared error loss. Introducing independent conjugate priors, a batch sequential procedure is proposed and compared with the optimal.